2013
DOI: 10.1007/s11033-013-2831-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression characterization of the chicken Piwil1 gene

Abstract: Piwi gene involves in the germline stem cells self-renewal, transposon silencing and post-transcriptional gene regulation in the majority of organisms; however, the biological function of Piwi gene in poultry remains unclear. Here we cloned the Piwi-like 1 (Piwil1) gene and characterized its expression in the Langshan chickens during the development. The results showed that the PIWIL1 protein was the homolog of mice MIWI and human HIWI proteins (100 % identity), and encoded a cytoplasmic protein including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In many other mammalian species, PIWIL1 expression is highly restricted to the testes in both developing and mature animals [27,45,46,57]. The pattern of PIWIL1 expression reported here is consistent with that reported in other species using either an N-terminal or C-terminal-specific antibody.…”
Section: Discussionsupporting
confidence: 89%
“…In many other mammalian species, PIWIL1 expression is highly restricted to the testes in both developing and mature animals [27,45,46,57]. The pattern of PIWIL1 expression reported here is consistent with that reported in other species using either an N-terminal or C-terminal-specific antibody.…”
Section: Discussionsupporting
confidence: 89%
“…In avian species, the biological functions of PIWI family members remain unclear. In recent studies, we characterized the chicken PIWI members CIWI and CILI (Kim et al, ), and revealed the complete genomic structure of the CIWI gene, including a 161‐bp fragment of the 5'‐UTR and 660 bp of the 3'‐UTR followed by a poly(A) tail (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PCR products of the correct size were cloned into the pGEM T easy vector (Promega, Madison, WI). A 4‐kb genomic fragment from −3,839 to +161 bp, including the predicted transcription start site, was cloned, but the +1 to +161‐bp region includes the 5'‐UTR and does not include the ATG start codon (Chen et al, ). The eGFP‐coding sequence and polyadenylation (poly‐A) tail were inserted into the cloned vectors containing the CIWI promoter using restriction enzymes Spe I and Nde I.…”
Section: Methodsmentioning
confidence: 99%
“…there are three types of PIWI proteins in mouse which are associated with piRNAs and expressed in male mouse germline and they are essential for fertility (Carmell et al, 2007). In chicken there is not enough studies about biological function of PIWI proteins however in a study PIWI like1 was detected in chicken and it was suggested that it has more expression in gonad and pays roles in myosis I (Chen et al, 2013). VASA protein belongs to the Dead-box helicase (DDX) family (Lasko & Ashburner, 1988).…”
Section: Important Genes Regulating Pgcs Specificationmentioning
confidence: 99%